2013
DOI: 10.1128/iai.00428-13
|View full text |Cite
|
Sign up to set email alerts
|

Cytoadherence of Plasmodium berghei-Infected Red Blood Cells to Murine Brain and Lung Microvascular Endothelial CellsIn Vitro

Abstract: dSequestration of infected red blood cells (iRBC) within the cerebral and pulmonary microvasculature is a hallmark of human cerebral malaria (hCM). The interaction between iRBC and the endothelium in hCM has been studied extensively and is linked to the severity of malaria. Experimental CM (eCM) caused by Plasmodium berghei ANKA reproduces most features of hCM, although the sequestration of RBC infected by P. berghei ANKA (PbA-iRBC) has not been completely delineated. The role of PbAiRBC sequestration in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 86 publications
(118 reference statements)
0
41
0
2
Order By: Relevance
“…IL-10 suppresses a Th1 response and has been shown in multiple studies to play a major role in preventing ECM (28,33,34,75). To investigate whether STAg-induced protection against ECM requires IL-10, we infected IL-10 Ϫ/Ϫ mice with P. berghei ANKA and treated mice with STAg after 24 h. STAg treatment was just as effective in wild-type (wt) and IL-10 Ϫ/Ϫ mice, as evidenced by similar percent survivals (Fig.…”
Section: Stag Treatment Alone and Stag Treatment Of P Berghei-infecmentioning
confidence: 99%
“…IL-10 suppresses a Th1 response and has been shown in multiple studies to play a major role in preventing ECM (28,33,34,75). To investigate whether STAg-induced protection against ECM requires IL-10, we infected IL-10 Ϫ/Ϫ mice with P. berghei ANKA and treated mice with STAg after 24 h. STAg treatment was just as effective in wild-type (wt) and IL-10 Ϫ/Ϫ mice, as evidenced by similar percent survivals (Fig.…”
Section: Stag Treatment Alone and Stag Treatment Of P Berghei-infecmentioning
confidence: 99%
“…In accordance with the bacterial colonization capacity in vivo, we used the human laryngeal carcinoma cell line HEp-2 and mouse brain microvascular endothelial cells (bEnd.3) as in the models of bacterial colonization (19,20,23) and meningitis (24,25) in vitro, respectively. The adherence assays were performed as previously described (26).…”
mentioning
confidence: 99%
“…Plasmodium species incapable of forming knobs in infected erythrocytes (knobless Plasmodium) show a passive adhesion of infected RBCs to activated endothelial cells [75]. Thus, knobless Plasmodium activates endothelial cells to the same extent as knob-forming Plasmodium [66,73], which suggests that ECM may also be induced by parasitized erythrocytes.…”
Section: Inflammatory Components In the Development Of Cerebral Malariamentioning
confidence: 99%
“…Several findings observed in human cerebral malaria are also observed in experimental models, including cytokine activity [70], endothelial activation [71], and edema formation [72]; however, the sequestration of parasitized erythrocytes during experimental cerebral malaria (ECM) is not well understood. Recent evidence showed that Plasmodium berghei-ANKA infected RBCs adhere to brain microvascular endothelial cells in a VCAM-1-dependent manner [73]. In addition, another study suggests transient contact between infected RBCs and the endothelium [74].…”
Section: Inflammatory Components In the Development Of Cerebral Malariamentioning
confidence: 99%